Exploring homelessness and Indigenous food Systems in northern British Columbia - Julia Russell; Margot W. Parkes (Canadian Food Studies / La Revue canadienne des études sur l'alimentation, 2018)
People experiencing homelessness are known to be highly food insecure, but outside of emergency aid little is known about their overall experiences with food, particularly in Canada’s northern communities. This study examined experiences that influenced access to food for people experiencing homelessness in a small city in northern British Columbia. Early findings underscored the importance of the impacts of colonization when seeking to understand food access in this context, and the value of lived experiences (including people with experiences of homelessness) when seeking to understand Indigenous food systems and food sovereignty as part of a re-emerging food system. The research drew on ethnography and case study methodology with modified community mapping to explore the food systems of the participants, who identified as First Nations, Métis or had mixed Indigenous and European ancestry. A focus group and subsequent interviews revealed a dynamic and complex food system. The flexible research design enabled participants to creatively express the food-related issues, challenges and successes most pertinent to their lives. Key food-related themes were social connections, as well as connections to the land and to culture. Participants’ experiences, actions and desires regarding food, health and well-being highlighted Indigenous food sovereignty as an overarching concept which offers an adaptable, holistic approach that can accommodate complexity. It is a valuable direction for future research and practice seeking to improve food security and health.